Epistemic merit, autonomy, and testimony - Jesús VEGA ENCABO (Theoria, 2008)
In this paper, it is argued that both the informer and the hearer in a testimonial situation deserve epistemic merit insofar as they contribute to the collaborative achievement of sharing knowledge. The paper introduces a distinction between the ideals of self-sufficiency and epistemic autonomy. The autonomous exercise of our epistemic agency is very often carried out under strong conditions of epistemic dependence. Testimony exhibits a kind of social dependence that does not threaten the autonomy of the subjects that need to consider their own epistemic capacities. When involved in a testimonial situation, both speaker and hearer declare, at least implicitly, the standings they occupy in an epistemic space and are obliged to recognise certain epistemic requirements.